Penerapan E-Learning Dalam Upaya Meningkatkan Kemampuan Komunikasi Matematis Mahasiswa - Supianti, In In (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
The aim of this study is to examine the problem of improving mathematical communication ability of students through the implementation of e-learning in mathematics. The research method in the form of a quasi-experimental study using pretest-posttest design. The population is student of Mathematics Education University of Pasundan, while the second semester student is sample, class A as a control class and class B as a experiment class. The instrument used in this study is 6 numbers of mathematical communication ability test and observation sheet. The results obtained are the improvement of communication skills students acquire mathematical study of mathematics by using e-learning better than students who use conventional learning.